Consumer cynicism in service failures. Issue 2 (6th October 2021) - Tran, Hai‐Anh; Strizhakova, Yuliya; Usrey, Bryan; Johnson, Samuel
Abstract: Despite growing corporate commitments to being customer‐centric, many customers perceive firms as self‐driven and caring only about their own business interests. This sentiment is projected in consumer cynicism, or negative consumer attitudes based on the disbelief in the sincerity of firms' motives and actions. We argue that consumer cynicism emerges in response to negative marketplace situations, such as service and product failures. Across four scenario‐based experiments and one video‐based experiment, our research examines cynicism as a key mediator, transmitting the effect of double deviation (i.e., a failure in delivery and in subsequent recovery) on negative electronic word‐of‐mouth and repurchase intention. We further demonstrate that consumer cynicism can be minimized when the provider uses cocreated recovery (i.e., engages consumers in recovery) even if the recovery fails and when the provider offers a strong empathetic apology (either before or after recovery failure). Our research contributes to consumer and service recovery research by highlighting an important but overlooked role of consumer cynicism in the context of double deviation. We also offer managerial insights into cocreation and empathetic apologies as cost‐effective recovery strategies to minimize cynicism.